Prospects of treatment of progressive forms of multiple sclerosis by transplantation of stem cells (review) - T. V. Sorokovikova; A. M. Morozov; A. N. Kryukova; S. A. Naumova; M. A. Belyak (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Relevance. Multiple sclerosis is a global medical and social problem of our time. This is due to a decrease in the number of able-bodied population due to the onset of the disease in 20-40 years, steady progression, the appearance of persistent neurological symptoms and disability. Therapy with drugs that change the course of multiple sclerosis is not always effective for progressive forms of the disease. There are a large number of clinical trials of modern medicines and techniques that affect the main links of pathogenesis, aimed at combating further progression and reducing the existing neurological deficit. One of the promising and potentially effective methods is stem cell transplantation.The purpose of study. To analyze foreign publications on the use of stem cells for the treatment of multiple sclerosis: to assess the possibility, safety and prospects of using stem cell transplantation in patients with progressive multiple sclerosis resistant to standard therapy.Materials and methods. In the course of this study, foreign scientific articles were searched in the databases "Elibrary", "PubMed", "Cochrane Library". The analysis and generalization of data on the main etiopathogenetic mechanisms of multiple sclerosis development and methods of influencing them, on alternative methods of treating multiple sclerosis, properties of different types of stem cells, methods of transplantation, results of open clinical trials of stem cell transplantation in patients with multiple sclerosis.Results. Stem cell therapy can be used as an alternative method of treating progressive forms of multiple sclerosis. Several types of stem cells with individual properties and advantages were considered for clinical use. Autologous hematopoietic, mesenchymal, neuronal, embryonic and induced pluripotent stem cells are distinguished. Mesenchymal and hematopoietic stem cells have demonstrated the greatest therapeutic potential in clinical trials. The safety and good tolerability of transplantation of these cell types have been proven, but the effectiveness remains controversial. Clinical improvements were more often observed in patients of younger age, with a disease duration of less than 10, inefficiency in no more than two previous methods of treatment modifying the disease, and having a lower baseline EDSS score.Conclusion. Stem cell transplantation is indeed a promising method and can revolutionize the treatment strategy for neurodegenerative diseases. Clinically proven safety and efficacy make it possible to change the approach to therapy in relation to the progressive course of multiple sclerosis, to conduct large multicenter clinical trials to include the method in the treatment standards. The opportunity to stop the progression and prolong the relapse-free period makes it possible in the near future to eliminate the need to take drugs that change the course of multiple sclerosis, reduce their side effects on the body and return patients to their former lives. The full clinical effect of transplantation has yet to be demonstrated by further studies.